Conformational enhancement of fidelity in toehold-sequestered DNA nanodevices. Issue 38 (7th April 2020) - Bader, Antoine; Cockroft, Scott L.
Abstract : Simple design principles improve conformational stability and decrease strand leakage by two orders of magnitude. Abstract : The operation of DNA nanodevices is often limited by erroneous strand displacement. Here we demonstrate simple design principles that reduce such leakage by up to two orders of magnitude. Enhanced operational robustness against multiple spurious inputs was obtained by simply relocating toehold overhangs to external locations and strengthening adjacent G–C clamping.